The living Word of God : rethinking the theology of the Bible - Witherington, Ben, III, 1951- (Baylor University Press, 2007)
In this final installment of his trilogy on the central ordinances of the Christian faith (baptism, the Lord's Supper, and the proclamation of God's Word), Ben Witherington asks: What does it mean to call the Bible "God's word"? In doing so, he takes on other recent studies which downplay the connection between history and theology, or between historical accuracy and truth claims. The Bible is not merely to be viewed as a Word about God, Witherington argues. Instead, he says, the Bible exhorts us to see the Bible as a living Word from God. -- Publisher